Anti-Essentialism and Intersectionality - Grillo, Tina (Theorizing feminisms a reader, 2006)
'What is oppression ?' 'What should be done about it ?' Organized around these questions, Theorizing feminisms : a reader provides an overview of theoritical feminist writing about the quest for gender justice. Incorporating both classic and cutting-edge material, the reader takes into account the full diversity of women, highlighting the effects of race, ethnicity, nationality, class, sexuality, and religion on women's experience. Theorizing feminisms is organized into four sections and includes fifty-four essays. The first section introduces several basic concepts commonly employed when thinking about sexism - oppression, social construction, essentialism, intersectionality, gender, race, and class - and also raises questions about the perspective and legitimacy of the theorist. The second section surveys three approaches that attempt to characterize in a general way the source of injustice toward women : humanist feminism ('the sameness approach'), gynocentric feminism ('the difference approach'), and dominance feminism. Offering an alternate perspective, the third section introduces two 'localizing' approaches, grounded in postmodernism and identity politics, respectively. Skeptical of theories that attempt to analyze social phenomena across history and culture, authors in this section challenge, rather than answer, the text's organizing questions. The final section explores the relationship of feminism theory to three liberatory projects - postcolonialism, neo-materialism, and queer theory - that do not characterize themselves as feminist, yet take gender as a significant category of analysis. Each section opens with an introduction and each essay is followed by helpful study questions. the majority of the essays are presented in their entirety. Theorizing feminisms underscores the strong connection between feminist theory and practice by including essays that illustrate important political inspirations or applications of each theoritical approach. It also presents versions of the same approach from various points in history, revealing feminist theory to be dynamic and evolving, rather than static. Ideal for interdisciplinary courses in feminist theory, this volume will also serve as an invaluable reference for current and future generations of theorists."
Section: 1 vol. (XIX-564 p.) ; 24 x 19 cm
Keywords: 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; cours; discipline; essentialisme; intersectionnalité; justice sociale; phi4336; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; thématiques; théorie féministe

Nous, enfants d'homos homoparentalité: une génération témoigne - Kaim, Stéphanie (Éd. de La Martinière, 2006)
A partir d'une enquête menée en France et en Californie, l'auteure décrit les conditions d'accession à l'homoparentalité, depuis le milieu des années 1970. Elle donne la parole à de jeunes adultes élevés par des homosexuels pour mieux poser la question de l'éducation et de l'orientation sexuelle de ces enfants.
Section: 1 v. (171 p.) : couv. illustrations en coul. ; 19 cm
Keywords: 1900-1999; 1970-1979; LGBTQIA2+; amérique du nord; amériques; approches et analyses; californie; cours; discipline; europe; filiation; france; identités LGBTQIA2+; justice sociale; premier cycle; périodes historiques; queer; régions géographiques; shm4000; thématiques; états-unis

Aspiration, reunification and gender transformation in Jat Sikh marriages from India to Canada - MOONEY, NICOLA (Global Networks, 2006)
In this article I explore marriage as a strategy of family migration among a transnational community of middle-class Jat Sikhs. Family reunification and status aspirations are examined as central concerns of the transnational movement of Jat Sikhs from India to Canada. It is argued that Jat Sikh transnationalism and gender are mutually-constitutive: migration strategies can construct women, as well as men, as agents of marital citizenship, and in facilitating migration, transnational marriage may transform practices and notions of gender and status. The article is based on preliminary ethnographic research among Jat Sikh brides in Toronto and Vancouver, and forms part of a larger study of gender, modernity and identity in Indo-Canadian Jat Sikh marriages.
Keywords: amériques; anthropologie; approches et analyses; asie; canada; colombie-britannique; cours; discipline; famille; histoire et politique; inde; intersectionnalité; justice sociale; mariage; mariages transnationaux; migration; ontario; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques; toronto; vancouver

Grossesse hors mariage dans les familles haïtiennes - Raphaël, Frantz (Santé mentale au Québec, 2006)
Des grossesses précoces chez des jeunes adolescentes haïtiennes de Montréal entraînent des situations de crise qui touchent plusieurs familles, en plus d’interpeller et d’impliquer des intervenants de diverses disciplines. Le sujet, abordé dans un contexte transculturel, fait référence au biculturalisme haïtien, tant en Haïti qu’en terre étrangère. Dans cet article, l’auteur aborde plus particulièrement la situation des Haïtiens dans le contexte québécois. L’analyse de l’attitude des parents des deux groupes culturels, occidentalisé et créole, constitue une lumière médiatrice dans les relations d’aide ou d’intervention psychothérapeutique. Dans la communauté haïtienne, les problèmes d’identité culturelle d’une part, et, le manque d’affiliation à la famille, d’autre part, sont à la base des conflits entre parents et enfants. L’auteur conclut avec des propositions dans le but d’améliorer l’efficacité des interventions avec ces familles dans leur processus d’adaptation migratoire.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; conflit familial; cours; discipline; grossesse hors mariage; haïti; justice sociale; maternité; montréal; premier cycle; psychologie; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; sex2283; sexualité; thématiques

Conceituando Empoderamento na Perspectiva Feminista - Sardenberg, Cecília M B (2006)
Transcription d’une communication au séminaire International : « Trilhas do empoderamento de mulheres », Salvador da Bahia, 5-10 juin 2006.
Keywords: amérique latine; amériques; anthropologie; approches et analyses; brésil; cours; cycles supérieurs; discipline; empowerment; fem7000; inégalités; justice sociale; militance; mouvements sociaux; patriarcat; pratiques féministes; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sofia; systèmes d'oppressions; thématiques; épistémologie

Global Recognition of Human Rights for Lesbian, Gay, Bisexual, and Transgender People - Suzanne M. Marks (Health and Human Rights, 2006)
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amérique du nord; amériques; approches et analyses; corps; cours; discipline; féminisme décolonial; hétérosexisme; identités LGBTQIA2+; justice sociale; pol4022; premier cycle; périodes historiques; queer; régions géographiques; science politique; systèmes d'oppressions; thématiques; violences; états-unis